Itinerary planner for tourism mobile application with smart trip generation and social platform - Loh, Wai Leong (2022)
Itinerary planning is an important process before a traveler starts a trip. This is because travelers would wish their trips to go smoothly and so that they could enjoy themselves as much as possible. However, it is a complicated and time-consuming process if travelers do not know how to make the plans. Although travelers can search through the online resources, they may not fully explore the attraction or other worthwhile resources in the destination. Thus, the purpose of this project is to build an itinerary planner mobile application to provide a proper and easy tool for all travelers to make their plans before trips. The mobile application allows users to create a trip by entering the necessary data and managing it. Furthermore, there is an auto build route function that will help users compile the route of their trip. As a result, users can get the best route in the short time. If users are not satisfied with the arrangement, they are able to manage it by themselves. Nevertheless, the social platform is available in the itinerary planner mobile application. The social platform allows users to create posts, view posts and react toward the posts by liking the posts or commenting on them. This is a good start for all the users to get to know each other and share their travel experiences. Moreover, users are allow to promote their business by creating an attraction and publish to others.